Framework for conformity assessment based on an analogy with the Uncertainty Principle of Quantum Mechanics (FCAUP) - de Moraes, Celso Francisco [UNESP]; Silva, Messias Borges (Elsevier, 2018)
This paper aims to introduce an innovative framework, named FCAUP, for planning and implementing conformity assessment based on a conceptual analogy with Heisenberg's Uncertainty Principle of Quantum Mechanics. Conformity assessment is a very important issue in many different areas, such as, operations and quality management, international trade, sustainable development, and so on. FCAUP means “Framework for Conformity Assessment inspired by the Uncertainty Principle”. This original procedure employs quantitative and qualitative techniques for analysis, classification, purposive sampling and execution of double inspections in order to reduce the uncertainty in conformity assessment activities. Its preliminary evaluation has been performed by means of three simulations regarding conformity assessments in manufacturing industries. Simulation results suggest that FCAUP is a consistent method to be used in several categories of conformity assessment.
Keywords: Conformity assessment; FCAUP; Framework; Uncertainty principle analogy